Early‐life stress‐induced visceral hypersensitivity and anxiety behavior is reversed by histone deacetylase inhibition. Issue 12 (25th September 2015) - Moloney, R. D.; Stilling, R. M.; Dinan, T. G.; Cryan, J. F.
Abstract: Stressful life events, especially in childhood, can have detrimental effects on health and are associated with a host of psychiatric and gastrointestinal disorders including irritable bowel syndrome (IBS). Early‐life stress can be recapitulated in animals using the maternal separation (MS) model, exhibiting many key phenotypic outcomes including visceral hypersensitivity and anxiety‐like behaviors. The molecular mechanisms of MS are unclear, but recent studies point to a role for epigenetics. Histone acetylation is a key epigenetic mark that is altered in numerous stress‐related disease states. Here, we investigated the role of histone acetylation in early‐life stress‐induced visceral hypersensitivity. Interestingly, increased number of pain behaviors and reduced threshold of visceral sensation were associated with alterations in histone acetylation in the lumbosacral spinal cord, a key region in visceral pain processing. Moreover, we also investigated whether the histone deacetylase (HDAC) inhibitor, suberoylanilide hydroxamic acid (SAHA), could reverse early‐life stress‐induced visceral hypersensitivity and stress‐induced fecal pellet output in the MS model. Significantly, SAHA reversed both of these parameters. Taken together, these data describe, for the first time, a key role of histone acetylation in the pathophysiology of early‐life stress‐induced visceral hypersensitivity in a well‐established model of IBS. These findings will inform new research aimed at the development of novel pharmaceutical approaches targeting the epigenetic machinery for novel anti‐IBS drugs. Abstract : Here we show, for what is to our knowledge, the first time, that early‐life stress‐induced visceral hypersensitivity is associated with reduced histone acetylation in the lumbosacral spinal cord. Moreover, HDAC inhibition using suberoylanilide hydroxamic acid (SAHA) was found to normalize the effects of early‐life stress in adulthood. These data highlight the role of histone acetylation in visceral pain processing and the novel use of HDAC inhibitors as potential anti‐IBS therapeutics.